An analysis of the effects of aromatherapy abdominal massage on menstrual discomfort relief - Lee, Su-Jung; Lee, Myung-Sun (Edelweiss Applied Science and Technology, 2025)
This study aimed to examine the effects of an aromatherapy-based intervention on relieving menstrual pain and discomfort in women suffering from premenstrual syndrome (PMS). Participants were divided into three groups: Experimental Group 1 received self-administered abdominal massage using a blend of essential oils (lavender, clove, black pepper, and clary sage) diluted in a carrier oil; Experimental Group 2 received massage with carrier oil only; and the control group applied a hot pack. The results showed that pain levels were lowest in Experimental Group 1, indicating that abdominal massage with aromatherapy can be an effective method for alleviating dysmenorrhea and menstrual discomfort. This intervention is expected to contribute to promoting the health and quality of life of women experiencing menstrual pain. The findings suggest that aromatherapy-based abdominal massage may serve as a practical approach for the management of dysmenorrhea and the enhancement of overall women’s health.